The global third way debate - Giddens, Anthony (Cambridge : Polity, 2001)
Modernizing left of centre governments are currently in power in many countries across the world. In greater or lesser degree, all have moved away from traditional doctrines and policies of the left, recognising that left values have to be pursued by different means today. The term 'third way' has become a widely accepted, if controversial, label understood by many modernizing social democrats to refer to these attempts at ideological andpolicy innovation. The debate that has arisen around these developments is a truly world-wide one, stretching from the US and Europe through to Asia, Australasia and Latin America. Anthony Giddens has been perhaps the foremost contributor to the global third way discussion. In this book he has brought together some of the key contributions from around the world. Articles included cover, among other topics: the development of the third way policies in EU countries; welfare institutions and welfare reforms; economic and social policy; trust, the civic order and government; the strains and stresses of democracy; the regulation of corporate power; ecological modernization; the third way viewed from the South; global governance. This book will be of interest to everyone concerned with the future of progressive politics. It provides perhaps the most comprehensive and integrated account to date of core developments in left of centre political thinking.r blind?
Includes bibliographical references and index.
English.
Keywords: Post-communism.; Globalization